Baleias em circulação: Uso de imagens na produção e transferência de conhecimentos de história natural marinha em Portugal do Século XVIII - Brito, Cristina; Costa, Lese (Arquivos de Zoologia, 2016)
News about exotic large marine animals started to spread around Europe since the second half of the 16th century. These, containing both written and visual information, were typically included in encyclopedias and treaties, but also in pamphlets that easily moved from one person to another, disseminating the available information through distinct nets of knowledge and to different audiences. By the 18th century, both as part of newspapers and pamphlets, information about strange natural events were amply printed and translated in several vernacular languages. These became increasingly of great interest to common people and not only to scholars, naturalists or collectors, but also practitioners and craftsmen. Printed news included records and rare occurrences of local and exotic fauna. The analysis of Portuguese sources contributed with good examples of such events, firstly published in Portugal and then copied and translated to other vernacular tongues. It is the case of a fin whale stranded in the Tagus estuary (Lisbon) reported in the Gazeta de Lisboa 1723 with a detailed description of the specimen, accompanied by an illustration of the whale with its measures, which was afterwards translated and printed in a German pamphlet. Here, the transfer of natural history accounts and communication of new concepts of the natural world was conducted from the periphery to the centre of Europe. Other news of large marine animals stranding on the Portuguese shore and respective illustrations were also produced. All together they seem to show the interest of all levels of the society for such rare and strange events. Moreover, these whales in pamphlets and in other publications contribute to the construction of a modern European concept of the natural world.